The Role of Tablets in the Development of a Bilingual Case in a Monolingual Society - Ubais Al-Azzawi , Qassim; Jreinikh Nayef, Karim (International Journal of Psychosocial Rehabilitation, 2020)
This case study deals with the relationship between specific socio-psychological factors and the development and maintenance of two languages (Arabic and English). Especially, the study examined the influence of the constant use of tablets in the development of an American English-speaking child in an Iraqi Arabic-speaking family. The case then developed into a multilingual one at the age of five. The subject of the paper is a six-year-old Iraqi child who was born to and raised by his Iraqi family. All the members of the family speak no other language than the southern Iraqi dialect. One of the researchers, the child’s father, is in constant contact with the child. He gathered his information through constant observation.